2018
DOI: 10.1161/jaha.118.008681
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Cholesterol Efflux Capacities in Patients With Coronary Artery Disease Undergoing Lifestyle Modification Therapy

Abstract: BackgroundOur objective was to identify the determinants of high‐density lipoprotein cholesterol efflux capacity (HDL‐CEC) changes in patients with coronary artery disease who participated in a lifestyle modification program aimed at increasing physical activity levels and improving diet quality.Methods and ResultsA total of 86 men with coronary artery disease aged between 35 and 80 years participated in a 1‐year lifestyle modification program that aimed to achieve a minimum of 150 minutes of aerobic physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Variation in the relative phospholipid and cholesterol content in large particles in a lean cohort as compared to persons with obesity or type 2 diabetes, has been linked to the inverse association of large HDL with c-fPWV [29]. Recent longitudinal analyses in men with CVD undergoing lifestyle modification therapy also suggest that HDL-c and the closely associated large HDL-P levels best predict ex vivo HDL cholesterol efflux capacity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the relative phospholipid and cholesterol content in large particles in a lean cohort as compared to persons with obesity or type 2 diabetes, has been linked to the inverse association of large HDL with c-fPWV [29]. Recent longitudinal analyses in men with CVD undergoing lifestyle modification therapy also suggest that HDL-c and the closely associated large HDL-P levels best predict ex vivo HDL cholesterol efflux capacity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been associated with an increase high-density lipoprotein (HDL) cholesterol, decreased triglycerides, and decreased non-HDL. 29,30 Hypertension has also been improved through physical activity, including lowering of both systolic and diastolic measures. 31 The recent narrative review complied 27 random control trials, results indicated moderate-to-vigorous physical activity led to the greatest reduction of blood pressure compared with resistance training.…”
mentioning
confidence: 99%